2023
DOI: 10.3390/su15043629
|View full text |Cite
|
Sign up to set email alerts
|

A BIM–LCA Approach for the Whole Design Process of Green Buildings in the Chinese Context

Abstract: The integrated description of the building geometry and the element attributes of the building information model (BIM) can reduce the effort needed to acquire data for life cycle assessment (LCA) and life cycle costing (LCC) at each design stage while supporting their potential for analyzing life cycle performances and feeding back to the design process. To support this, several methods and tools have been proposed that aim to obtain the life cycle performances of buildings following the level of model fidelit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…First, it provides accurate and detailed information about building systems, such as HVAC, lighting and energy usage, which can help optimize building performance (Choi and Lee, 2023). Building designers can use this information to make more informed decisions regarding building design, energy efficiency and resource usage, resulting in sustainable and environmentally friendly buildings (Choi and Lee, 2023;Li et al, 2023). Ferreira et al (2023) examined the impact of design optimization using BIM and concluded that enhanced energy consumption can result in a 2%-5% total savings (Ferreira et al, 2023).…”
Section: Safety and Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…First, it provides accurate and detailed information about building systems, such as HVAC, lighting and energy usage, which can help optimize building performance (Choi and Lee, 2023). Building designers can use this information to make more informed decisions regarding building design, energy efficiency and resource usage, resulting in sustainable and environmentally friendly buildings (Choi and Lee, 2023;Li et al, 2023). Ferreira et al (2023) examined the impact of design optimization using BIM and concluded that enhanced energy consumption can result in a 2%-5% total savings (Ferreira et al, 2023).…”
Section: Safety and Environmentmentioning
confidence: 99%
“…The full terms of this license may be seen at http://creativecommons.org/licences/by/4.0/legalcode BIM investment value projects through the use of three-dimensional (3D) models (Condotta and Scanagatta, 2023;Hasanain and Nawari, 2022). As part of the BIM-based project management process, a 3D model is created which contains information on the geometric and non-geometric attributes of the building, as well as digital replicas of products from the manufacturer (Li et al, 2023). Data are gathered into a shared data environment in which all project information is kept up-to-date and communicated to stakeholders in order to ensure the highest level of resource efficiency throughout the project life cycle (Feng et al, 2023;Lu et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…The extended time frame can increase costs as well, potentially diminishing the appeal of these methods for the cost-conscious building sector [38]. However, by combining Building Information Modeling (BIM) and LCA, it is possible to reduce the amount of work required to obtain data at each stage of the building design, thereby mitigating the shortcomings of the time-consuming LCA evaluation process, and achieving a dynamic synergy between design and evaluation through the generation of models [40]. In addition, BIM-LCA research can assist designers in optimizing the design of sustainable building solutions, which take into account the environmental impact of building materials and operations [41].…”
Section: Project Managementmentioning
confidence: 99%
“…In order to promote the application of BIM in the design of prefabricated buildings, Bhola J compared the BIM of collaborative design with traditional design methods and established a conceptual model of PCP collaborative design based on the requirements of the IDM BIM technology to determine the accuracy of the BIM model in different design stages [22]. Aiming at the process of green building design in China, Li Q et al proposed an extensible LCA/LCC method combined with the BIM platform and implemented the method with tools developed based on Revit [23]. Abd Razak studied the benefits of BIM integration with DfMA (Design for manufacturing and assembly).…”
Section: Introductionmentioning
confidence: 99%